A primer of conservation genetics - Frankham, Richard, 1942- (Cambridge University Press, 2004)
For those with a limited background in genetic studies, this entry level text is presented in an easy-to-follow format with main points and terms clearly highlighted. Worked examples are provided throughout to help illustrate key equations and a glossary and suggestions for further reading provide additional support.